Transverse Carpal Ligament and Forearm Fascia Release for the Treatment of Carpal Tunnel Syndrome Change the Entrance Angle of Flexor Tendons to the A1 Pulley: The Relationship between Carpal Tunnel Surgery and Trigger Finger Occurence - Nazım Karalezli; Harun Kütahya; Ali Güleç; Serdar Toker; Hakan Karabörk; Tunc C. Ogun (The Scientific World Journal)
Purpose. The appearance of trigger finger after decompression of the carpal tunnel without a preexisting symptom has been reported in a few articles. Although, the cause is not clear yet, the loss of pulley action of the transverse carpal ligament has been accused mostly. In this study, we planned a biomechanical approach to fresh cadavers. Methods. The study was performed on 10 fresh amputees of the arm. The angles were measured with (1) the transverse carpal ligament and the distal forearm fascia intact, (2) only the transverse carpal ligament incised, (3) the distal forearm fascia incised to the point 3 cm proximal from the most proximal part of the transverse carpal ligament in addition to the transverse carpal ligament. The changes between the angles produced at all three conditions were compared to each other. Results. We saw that the entrance angle increased in all of five fingers in an increasing manner from procedure 1 to 3, and it was seen that the maximal increase is detected in the middle finger from procedure 1 to procedure 2 and the minimal increase is detected in little finger. Discussion. Our results support that transverse carpal ligament and forearm fascia release may be a predisposing factor for the development of trigger finger by the effect of changing the enterance angle to the A1 pulley and consequently increase the friction in this anatomic area. Clinical Relevance. This study is a cadaveric study which is directly investigating the effect of a transverse carpal ligament release on the enterance angle of flexor tendons to A1 pulleys in the hand.